Control of Converter for a Solar PV-BESS Powered Telecom Load With Real, Reactive and Harmonic Power Exchange With Grid - V. Sheeja; R. Kalpana; Umashankar Subramaniam; Dhafer J. Almakhles (IEEE Access, 2023)
Due to safety considerations and the challenges involved in tracking the maximum output of series-connected cells, solar photovoltaic (PV) arrays are generally operated at lower voltage levels. A multiport converter can be used to interface telecom DC loads, typically rated at 48 V and powered by PV arrays and battery energy storage system (BESS). The grid integration of the system improves reliability while lowering the BESS rating. This work proposes a sliding mode control-based power flow management controller that maintains the load voltage of a telecom DC load, allows maximum power extraction from the PV module, and facilitates power sharing with AC grid. A voltage source converter and a high-gain bidirectional converter exchange power with the AC grid. A second-order generalized integral algorithm-based voltage source converter control is provided to inject/absorb active power, reactive power, and eliminate the harmonics of the telecom AC load. Detailed simulation studies employing MATLAB software are performed to validate the functionality of the converter as well as the power flow management control. Moreover, the system’s performance is evaluated using a laboratory-developed experimental prototype.